The Marks of Civilisation: The Special Stigma of Torture. (11th December 2021) - Farrell, Michelle
Abstract: The European Court of Human Rights attached a special stigma to torture in Ireland v United Kingdom, in its interpretation of the distinction between torture and other forms of ill-treatment. The concept is now central to the European Court's description of torture under article 3 of the European Convention on Human Rights. It is, I argue, significant that the Court reached for this particular phrase. I consider the special stigma as a parapraxis facilitating a reading of the Court's 'unconscious text'. I connect the power to stigmatise with torture to explore the special stigma's figurative, material and theological implications. Stigma, with its multi-layered meaning and its deep connections to torture, is useful in working out how Western powers generated their self-images as civilised whilst persisting with practices of torture. With the special stigma, the European Court rehabilitated the civilising standard and resurrected the historic association between torture and stigma.